Impactos a jusante de barragens : mudanças nas assembleias de peixes invertívoros. - Granzotti, Rafaela Vendrametto (2018)
Impoundments alter connectivity, sediment transport and water discharge in rivers and floodplains, affecting fish habitat, resource availability and recruitment, including for benthic invertivorous fish, which represent an important link between primary producers and higher trophic levels in tropical aquatic ecosystems. We investigated long-term changes to water regime, limnological features and invertivore assemblages pre and post impoundment in three rivers downstream of a major dam. Impacts were distinct in the Paraná River that is obstructed by the dam, less evident in the Baía River, also impounded, but absent in the unimpounded Ivinhema River. Changes in water regime were reflected mainly by variables of water-level magnitude, whereas variables of water-level timing showed little alteration. Water transparency increased in the Paraná River post dam but did not change in the Baía and Ivinhema rivers. Changes in fish assemblages included a decrease in catch rate of invertivores in the Paraná River and a shift in relative species composition in the Baía and Paraná rivers but not in the unimpounded Ivinhema River. Changes in water regime and water transparency, caused by impoundment, directly or indirectly impacted invertivores assemblages. Alterations of fish assemblages following environmental changes have consequences over the entire ecosystem, including a potential decrease in the diversity of mechanisms for energy flow. We suggest that keeping existing unimpounded tributaries free of dams, engineering artificial floods, and intensive management of fish habitat within the floodplain may preserve native fish assemblages and help maintain functionality and ecosystem services in highly impounded basins.